Survey of health care student attitudes towards transgender health care education (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Background: This study assessed health care trainees perceptions of their education regarding transgender health care issues and personal and professional comfort level with the provision of transgender health care. An online 20 question survey (2013) about trainee experience and education on transgender health care was administered to medical (MD), nurse practitioner (NP), and physician assistant (PA) students at a single institution. Methods: The survey instrument consisted of seven demographic questions and 13 non-demographic questions about education in transgender health, hours of education received, and personal and professional comfort with transgender medical care. Non-demographic questions were written as even-point Likert scale questions with four rating options (very comfortable, somewhat comfortable, somewhat uncomfortable, and very uncomfortable). Results: A total of 484 MD, NP, and PA students responded to the online survey out of 1,035 eligible students (47% response rate). Only 74 (15%) respondents had provided medical care to a transgender patient. Provision of medical care to a transgender patient was associated with increased hours of education on transgender health issues (P
Keywords: transgender; education; health care; student